2015
DOI: 10.1016/j.juro.2015.02.2938
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Resonance Imaging Targeted Biopsy Improves Selection of Patients Considered for Active Surveillance for Clinically Low Risk Prostate Cancer Based on Systematic Biopsies

Abstract: Magnetic resonance imaging targeted biopsy reclassified 10% of patients who were eligible for active surveillance based on systematic biopsy. Its incorporation into the active surveillance eligibility criteria may decrease the risk of reclassification to higher stages during followup.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(48 citation statements)
references
References 30 publications
2
44
0
Order By: Relevance
“…In recent years, mpMRI and mpMRI/TRUS fusion targeted biopsy have a good degree of accuracy in diagnosing clinically significant PCa secondary to the high sensitivity for lesion upgrading [8][9][10][11], especially when the cancer is located in the anterior prostate [6,7] or in the presence of micro-focal PCa (1 positive core of GS and GPC ≤ 5 %) [21]. Ouzzane et al [24] reporting on 281 patients in AS found that mpMRI targeted biopsy reclassified 10 % of patients who were eligible for AS based on systematic biopsy. Kamrava et al [25] in a series of 245 patients with a diagnosis of low-risk PCa enrolled in an AS protocol reported that at confirmation biopsy 24 % were upgraded using MRI fusion biopsy versus 14 % using standard transrectal biopsy, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, mpMRI and mpMRI/TRUS fusion targeted biopsy have a good degree of accuracy in diagnosing clinically significant PCa secondary to the high sensitivity for lesion upgrading [8][9][10][11], especially when the cancer is located in the anterior prostate [6,7] or in the presence of micro-focal PCa (1 positive core of GS and GPC ≤ 5 %) [21]. Ouzzane et al [24] reporting on 281 patients in AS found that mpMRI targeted biopsy reclassified 10 % of patients who were eligible for AS based on systematic biopsy. Kamrava et al [25] in a series of 245 patients with a diagnosis of low-risk PCa enrolled in an AS protocol reported that at confirmation biopsy 24 % were upgraded using MRI fusion biopsy versus 14 % using standard transrectal biopsy, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Even more recently the combination of MRI/Ultrasound (MRI/US) guided platforms provides the ability to overlay MP-MRI images in real time on TRUS, and thus perform more targeted biopsies. This targeting allows for the diagnosis of more high-risk cases and fewer low-risk cases of prostate cancer in comparison to standard sextant biopsy [6,7], as well as track lesions over time with imaging or repeat biopsy, through active surveillance (AS) [8,9]. Targeted MRI/US guided biopsy is an emerging technology that has the potential to change standard of care for the diagnosis and management of prostate cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Other data confirm this by showing a low relative sensitivity ratio of 0.33 for the detection of Gleason score ≥7 PCa in mpMRI compared to sysPbx [32]. In contrast, other study groups demonstrated that mpMRI and targeted biopsy mainly contributed to the Gleason score upgrading, whereas sysPbx did not lead to an upgrading [33]. In Table 4.…”
Section: Discussionmentioning
confidence: 79%